Dynamics Of Co-Infectious Childhood Respiratory Diseases: Pertussis And Pneumonia - Yakubu, Aisha Aliyu (2023)
Pertussis is a vaccine-preventable respiratory disease that affects humans of all age groups, yet there are reported cases of resurgence. The disease is highly contagious and has posed detrimental effects on the lives of infants globally. The impact of pertussis worsened with the presence of viral infections such as pneumonia. Therefore, it is imperative to study the behavior of these diseases and suggest control strategies using a mathematical modeling approach. The study area and literature of mathematical models on pertussis and pneumonia co-infection dynamics is rather scanty. Therefore, this study is aimed at obtaining model equations using a system of nonlinear ordinary differential equations for a better understanding of the transmission dynamics and control of these diseases in the infant population. Further, the models are used to evaluate the intervention strategies for disease control. The first model is the general model describing the transmission dynamics of pertussis which incorporates a maternally derived immunity compartment. The dynamical behavior of the basic model is analyzed analytically and numerically. Numerical simulations were carried out using mathematical software. The basic reproduction number of the model is obtained and its behavior is analyzed by varying parameters.